Serum Ferritin and Procalcitonin as Diagnostic Biomarkers for Sepsis in an Emergency Department: A Clinical Study - Sreejith R. Nair; M. T. Manoj; Sohanlal Thiruvoth (Archives of Medicine and Health Sciences)
Background and Aim: Sepsis, a life-threatening condition, presents diagnostic challenges due to its heterogeneous nature. Early and accurate diagnosis is essential for timely intervention. Serum biomarkers, such as ferritin and procalcitonin (PCT), have been explored for their potential in sepsis diagnosis, but the outcomes are inconclusive. The current study was an attempt to further explore the usefulness of ferritin and PCT as sepsis biomarkers. Material and Methods: A prospective study involving 149 patients assessed serum ferritin and PCT levels in those with features suggestive of sepsis. Patients were categorized into sepsis and nonsepsis groups based on the clinical judgment of the emergency physicians. Statistical analyses, including the Mann–Whitney U test and receiver operating characteristic (ROC) curves, were conducted to evaluate the diagnostic utility of these biomarkers. Results: Serum ferritin levels did not exhibit a statistically significant difference between sepsis and nonsepsis groups (P = 0.698). In contrast, PCT levels were significantly higher in sepsis cases (P = 0.011). ROC analysis identified an optimal PCT cutoff value of 0.085, offering high sensitivity (92.5) but lower specificity (16.7). Conclusion: PCT proved valuable as a diagnostic marker for sepsis. Serum ferritin, on the other hand, did not demonstrate statistical significance as a diagnostic marker for sepsis, its potential role in specific septic conditions and disease severity monitoring warrants further investigation.